Adopting orphan deceased donor kidneys for transplantation - Armando Salim Munoz-Abraham; Mahmoud Morsi; Angel Alvarez; Jeffrey J. Gaynor; Giselle Guerra; Adela Mattiazzi; Rodrigo Vianna; Gaetano Ciancio (BMC Nephrology)
Abstract Background Kidney transplantation is the best option for overcoming kidney replacement therapy in the end stage kidney disease population. Yet the number of available kidney donors remains limited. The use of aggressive kidney offers could serve as an alternative to address the shortage of donors and reduce the rate organ non-use. Methods We retrospectively analyzed ten kidneys that were aggressively offered to our transplant center before being included in the non-usable organ pool. They were transplanted in a short period of time. Donor and recipient demographics, intraoperative data, and recipient outcomes were included in the analysis. Results Ten orphan kidneys were transplanted into appropriate recipients from three deceased kidney after cardiac death and three from brain death donors. The median cold ischemia time was 2,216 min, and median warm ischemia time was 25 min. Five recipients experienced delayed graft function. The median creatinine levels were 1.5 mg/dl, 1.5 mg/dL, and 1.4 mg/dL at 3, 6 and 12 months. Conclusions We successfully transplanted ten kidneys that otherwise would have been classified within the UNOS organ non-use rate. Several factors contributed to the successful utilization of these kidneys, including kidney biopsies, hypothermic machine perfusion, treatment during machine perfusion, and careful selection of appropriate recipients by the transplant team. The non-use kidney pool presents a valuable opportunity for enhancing kidney utilization for transplantation and increasing organ availability. Clinical trial number Not applicable.